1998
DOI: 10.1161/01.cir.98.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Characteristics of a Slow Posterior AV Nodal Pathway

Abstract: Background-The AV node is frequently the site of reentrant rhythms. These rhythms arise from a slow and a fast pathway for which the anatomic and functional substratum remain debated. This study proposes a new explanation for dual-pathway physiology in which the posterior nodal extension (PNE) provides the substratum for the slow pathway. Methods and Results-The anatomic and functional properties of the PNE were studied in 14 isolated rabbit heart preparations. A PNE was found in all studied preparations. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
93
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 81 publications
9
93
0
3
Order By: Relevance
“…3,[13][14][15][16][17][18][19]22,23,25 What Is the Atrial or Posterior Input to the AVN? A comparison of histological data for the atrial or posterior input identified by other workers with histological data presented here identifies these structures as ordinary myocardium of the medial atrial wall and, by and large, as various parts of its annular myocardium: terminals of internodal tracts (James,14 Figures 2B, 6, 7, and 9; James, 23 Figures 6C and 6D), the rightward component of the compact AVN (Becker and Anderson, 16 Figure 8A; Inoue and Becker, 19 Figures 2B, 3, and 5 to 7), the overlay and transitional myofibers (James, 14 Figures 2A and 3B; Becker and Anderson, 16 Figure 2A), with the posterior nodal extension and compact AVN (Medkour et al, 24 Figure 2) and the AV nodal ring input being analogous to part or all of the circumferential lamina encircling the tricuspid valve (McGuire et al, 25 Figures 11 and 12) and all of the ordinary atrial myocardium of the AV junction region (Sanchez-Quintana et al, 18 Figure 2). Moreover, the PAVB is aligned with the medial or upper leg of Koch's triangle (Figure 2A).…”
Section: Points Of Controversymentioning
confidence: 97%
See 2 more Smart Citations
“…3,[13][14][15][16][17][18][19]22,23,25 What Is the Atrial or Posterior Input to the AVN? A comparison of histological data for the atrial or posterior input identified by other workers with histological data presented here identifies these structures as ordinary myocardium of the medial atrial wall and, by and large, as various parts of its annular myocardium: terminals of internodal tracts (James,14 Figures 2B, 6, 7, and 9; James, 23 Figures 6C and 6D), the rightward component of the compact AVN (Becker and Anderson, 16 Figure 8A; Inoue and Becker, 19 Figures 2B, 3, and 5 to 7), the overlay and transitional myofibers (James, 14 Figures 2A and 3B; Becker and Anderson, 16 Figure 2A), with the posterior nodal extension and compact AVN (Medkour et al, 24 Figure 2) and the AV nodal ring input being analogous to part or all of the circumferential lamina encircling the tricuspid valve (McGuire et al, 25 Figures 11 and 12) and all of the ordinary atrial myocardium of the AV junction region (Sanchez-Quintana et al, 18 Figure 2). Moreover, the PAVB is aligned with the medial or upper leg of Koch's triangle (Figure 2A).…”
Section: Points Of Controversymentioning
confidence: 97%
“…Although the same plane of section was used, major discrepancies are still apparent in schematics of the AV junction region 14 -16,18,19,22 and in different studies by the same workers. 16,19,23,24 The real AV junction region tissues were revealed by (1) preservation of the hearts with a protocol that maintains the ultrastructural integrity of paraffinembedded tissues (Racker,12 Figures 1-8 to 1-11), (2) natural flattening of the hearts so that structures could be viewed in orthogonal planes at right angles to each other in 360 degrees, and (3) systematic study of the histological details of the entire AV junction region in 3 orthogonal planes in photomicrographs. A comparison of our data with that generated with conventional protocols reveals that the latter resulted in osmotic damage with a loss of cytoplasmic (eg, Hudson, 3 Figures 2-12C and 2-13C; James, 14 Figures 3B and 3D; and Becker and Anderson, 16 Figure 10) and interstitial (eg, James, 14 Figure 3; McGuire et al, 25 Figures 12 and 13; and Medkour et al, 24 Figure 2) details.…”
Section: Points Of Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The interatrial septum plays an important role in intra-atrial as well as interatrial conduction 4,5 and is involved in the initiation and maintenance of tachyarrhythmias such as atrioventricular nodal reentry tachycardia, 6,7 atrial flutter, 8,9 and atrial fibrillation. 10,11 Previous simultaneous mapping studies of the intact right atrium (RA) and the left atrium (LA) were limited to the epicardium, 12,13 whereas simultaneous multisite endocardial mapping studies were performed only in the RA.…”
mentioning
confidence: 99%
“…12 The transitional cell envelope and inferior nodal extensions are not sheath-isolated conduction cables and, therefore, no sharp boundary can be drawn between them on the basis of cellular content. 13 The CCR in the rabbit heart, unlike those in human and dog hearts, 14 is located just after the penetration of the axis into the insulating tissues of the central fibrous body and should be considered a part of the penetrating bundle. We use the term AVN to describe all of the above components of the conduction axis.…”
Section: The Working Hypothesismentioning
confidence: 99%